Radiation chemical processes in the water layer on the surface of PuO2 - Sims, Howard E.; Orr, Robin M. (Frontiers in Nuclear Engineering, 2024)
It is generally accepted that radiolysis of water on the surface of PuO2 by alpha particles is the source of H2 which can cause pressurisation in sealed storage containers if the material is not adequately conditioned before packing. The mechanisms for this have not been discussed in detail previously. Radiolysis mechanisms of bulk water are summarised and then applied to water at the surface of PuO2. It is shown that the radiolysis processes occurring on timescales of less than 1 ps after energy deposition could have an impact on the storage behaviour of the PuO2 and the potential gas volume generated. Some of the radiolysis products are highly reactive and would be expected to react with plutonium at the surface, affecting the usual water radiolysis processes. A corollary of this observation is that the surface should not be considered a completely crystalline PuO2 solid. It is also highlighted that whilst there are significant uncertainties in the radiolysis process at the PuO2 surface there are also significant uncertainties in H2 formation mechanisms in bulk water. Finally, methods to model the radiolysis process at the surface and the prospects for predictive models are briefly discussed with suggestions for future areas of development.